New insights into the role of the CHI3L2 protein in invasive ductal breast carcinoma - Rusak, Agnieszka; Kątnik, Ewa; Górnicki, Tomasz; Schmuttermaier, Christina; Kujawa, Krzysztof; Piotrowska, Aleksandra; Ratajczak-Wielgomas, Katarzyna; Kmiecik, Alicja; Wojnar, Andrzej; Dzięgiel, Piotr; Kzhyshkowska, Julia (Scientific reports, 2024)
Chitinase-like proteins have multiple biological functions that promote tumor growth, angiogenesis and metastasis. Expression of CHI3L2, which is similar in structure to CHI3L1, is detected in glioma cells and tumor-associated macrophages (TAMs) in glioma and breast cancer. However, its exact role remains unclear. We analyzed the expression of CHI3L2 in 74 invasive ductal breast carcinoma (IDC) tumors, breast cancer and macrophages cell cultures using immunohistochemistry, immunofluorescence, Western blot and PCR methods. Clinicopathologic data were included in the analysis. The results obtained show that CHI3L2 expression decreases with increasing degree of tumor grade and negative status of estrogen (ER) and progesterone receptors (PR). Furthermore, CHI3L2 is significantly and positively correlated with phosphorylation of STAT-3 and ERK1/2 signaling pathways, but negatively correlated with macrophage infiltration. CHI3L2 is expressed both in the cytoplasm of cancer cells and in macrophages and may regulate STAT-3 and ERK1/2 phosphorylation in breast cancer cell lines. Analysis of the clinicopathologic data revealed that CHI3L2 levels had no effect on patient survival. CHI3L2 expression may be specific for cancer cells in IDC and involved in cross-talk with the tumor microenvironment. Our study has shown that IDC cancer cells express the CHI3L2 protein, possibly indicating a novel function of this protein.
Gesehen am 14.04.2025